The appropriateness of the reasonableness standard in ensuring the effective realisation of socio-economic rights in South Africa - Pillay, Rani (University of Pretoria, 2023)
Mini Dissertation (LLM (Socio-Economic Rights))--University of Pretoria, 2022.